Potency of Bioactive Compound of Rice Bran for Colon Cancer Prevention (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Colon cancer is the second leading cause of death in the world. Bioactive compounds in rice bran have a very active role as antiproliferation of colon cancer cells such as ferulic acid, p-coumaric acid, caffeic acid, gallic acid, protocatechuic acid, sinapic acid, tricin, luteolin, apigenin, myrecitin, rutin, isorhamnetin, Î³-oryzanol, Î³-tocopherol, Î´-tocopherol, Î³-tocotrienol, Î²-sitosterol, phytic acid, and hemicellulose. Mechanism of the bioactive compounds in cells varied, including modulation of a cell cycle, activation of immune cells, damage of a lipid layer and mitochondrial membrane, activation of caspase proteins, inhibition of protein cell tumor invasion, metastasis, and angiogenesis, and also acts as an antioxidant. Therefore, the existence of the scientific studies results of this review with the potential availability of adequate rice bran in Indonesia is very potential to be developed.